The impact of self-harm by young people on parents and families: a qualitative study. Issue 1 (6th January 2016) - Ferrey, Anne E; Hughes, Nicholas D; Simkin, Sue; Locock, Louise; Stewart, Anne; Kapur, Navneet; Gunnell, David; Hawton, Keith
Abstract : Objectives: Little research has explored the full extent of the impact of self-harm on the family. This study aimed to explore the emotional, physical and practical effects of a young person's self-harm on parents and family. Design and participants: We used qualitative methods to explore the emotional, physical and practical effects of a young person's self-harm on their parents and family. We conducted a thematic analysis of thirty-seven semistructured narrative interviews with parents of young people who had self-harmed. Results: After the discovery of self-harm, parents described initial feelings of shock, anger and disbelief. Later reactions included stress, anxiety, feelings of guilt and in some cases the onset or worsening of clinical depression. Social isolation was reported, as parents withdrew from social contact due to the perceived stigma associated with self-harm. Parents also described significant impacts on siblings, ranging from upset and stress to feelings of responsibility and worries about stigma at school. Siblings had mixed responses, but were often supportive. Practically speaking, parents found the necessity of being available to their child often conflicted with the demands of full-time work. This, along with costs of, for example, travel and private care, affected family finances. However, parents generally viewed the future as positive and hoped that with help, their child would develop better coping mechanisms. Conclusions: Self-harm by young people has major impacts on parents and other family members. Clinicians and staff who work with young people who self-harm should be sensitive to these issues and offer appropriate support and guidance for families.